AB1251 Neurological manifestations associated with anti-tumor necrosis factor alpha treatment. A longitudinal study. (23rd January 2014) - Kaltsonoudis, E.; Papagoras, C.E.; Konitsiotis, S.; Markatseli, T.E.; Zikou, A.K.; Argyropoulou, M.I.; Drosos, A.A.
Abstract : Background: Anti-tumor necrosis factor-α (TNFα) agents have been successfully used for the treatment of rheumatic diseases including rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS). Yet, several reports have been published that relate anti-TNFα therapy with the development of various neurological disorders, including peripheral neuropathy, multiple sclerosis, optic neuritis and acute transverse myelitis. However, whether TNFα blockers are directly causative or simply unmask occult underlying neurological disorders has not yet been elucidated. This is a longitudinal observational study of the incidence of neurological manifestations in patients with rheumatic diseases starting anti-TNFα treatment. Methods: Sixty-seven patients who were followed at a single tertiary Rheumatology center and who qualified for anti-TNFα treatment were included in the study. They were 38 males and 29 females, 32 had RA, 21 PsA and 14 AS. Exclusion criteria were: a history of atherothrombotic events, severe/uncontrolled hypertension, diabetes mellitus, previous head trauma or surgery or any other significant past neurological condition. At baseline, all patients underwent detailed physical, rheumatological and neurological clinical examination, brain magnetic resonance imaging (MRI) and electroencephalography (EEG). Neurological examination was repeated on every scheduled visit (approximately every 2-3 months), while brain MRI and EEG were repeated at 18 months or in case of neurological signs or symptoms, whichever occurred first. Results: All patients were anti-TNFα naïve, except for one with PsA who switched from etanercept to infliximab due to inadequate response. At baseline, no patient reported significant neurological symptoms and the neurological examination and EEG were normal. Of the 67 patients, two (one with AS and one with PsA) never received anti-TNFα therapy, because baseline brain MRI revealed definite or suspicious lesions of demyelinating disease. In the rest, 36 received infliximab, 15 adalimumab and 14 etanercept. One patient (the one who had switched from etanercept to infliximab) presented 8 months later with right Bell's palsy and concomitant right peroneal nerve palsy. MRI imaging revealed lesions compatible with demyelinating disease and infliximab was withdrawn. For the remaining 64 patients no clinical, EEG or MRI abnormalities were observed during the 18-month follow-up. Conclusions: Neurological manifestations may not be too uncommon in patients with rheumatic diseases, before and during anti-TNFα therapy. However, the frequency of neurological adverse events may be further suppressed, if the treatment is withheld in those patients with clinical and/or radiographic neurological abnormalities. Thus, a baseline brain MRI scan may be useful to rule out occult neurological disease. Disclosure of Interest: None Declared